2019
DOI: 10.1111/all.14039
|View full text |Cite
|
Sign up to set email alerts
|

Acid sphingomyelinase regulates TH2 cytokine release and bronchial asthma

Abstract: Background Allergic diseases and especially allergic asthma are widespread diseases with high prevalence in childhood, but also in adults. Acid sphingomyelinase (ASM) is a key regulator of the sphingolipid pathway. Previous studies defined the association of ASM with the pathogenesis of TH1‐directed lung diseases like cystic fibrosis and acute lung injury. Here, we define the role of ASM in TH2‐regulated allergic bronchial asthma. Methods To determine the role of Asm under baseline conditions, wild‐type (WT) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 50 publications
(103 reference statements)
0
15
0
Order By: Relevance
“…Acidic sphingomyelinase, which cleaves sphingomyelin to ceramide, has been implicated in bronchial asthma in mice. 45 However, in contrast to significant increases in ceramide and dihydroceramide levels, sphingomyelin levels were essentially unchanged after exposure to HDM (see Fig E5 in this article's Online Repository at www. jacionline.org), indicating that sphingomyelin degradation is not a major contributor to elevation of ceramide level.…”
Section: Allergen-induced Ros and Apoptosis Are Ceramide Dependentmentioning
confidence: 98%
“…Acidic sphingomyelinase, which cleaves sphingomyelin to ceramide, has been implicated in bronchial asthma in mice. 45 However, in contrast to significant increases in ceramide and dihydroceramide levels, sphingomyelin levels were essentially unchanged after exposure to HDM (see Fig E5 in this article's Online Repository at www. jacionline.org), indicating that sphingomyelin degradation is not a major contributor to elevation of ceramide level.…”
Section: Allergen-induced Ros and Apoptosis Are Ceramide Dependentmentioning
confidence: 98%
“…In contrast to that in the healthy control group, the serum ASMase activity in the asthma group was significantly reduced, but there was no significant difference in induced sputum supernatant ASMase activity between the two groups (Table 3). ASMase is thought to convert SM into Cer in the pathogenesis of asthma 11,37,38 . In this study, the SM level was found to be decreased in asthma patients, and thus, we speculated that ASMase activity may be up‐regulated in asthma patients.…”
Section: Resultsmentioning
confidence: 61%
“…ASMase is thought to convert SM into Cer in the pathogenesis of asthma. 11,37,38 In this study, the SM level was found to be decreased in asthma patients, and thus, we speculated that ASMase activity may be up-regulated in asthma patients. However, the results showed that the serum ASMase activity in asthma patients was lower than that in healthy controls.…”
Section: Differences In Asmase Activity Between Asthma Patients and Healthy Controlsmentioning
confidence: 50%
See 2 more Smart Citations